Accounting and environmental activity of the rum industry in Cuba: Case study Mixed Company Havana Club International S.A-Ronera San José - Marelis Albuerne Rizo; Nubia Venereo Collado (Contabilidad y Negocios: Revista del Departamento Académico de Ciencias Administrativas, 2017)
During the last years, the economic activity has generated a serious negative impact on the environment. In the current international scenario, characterized by a structural systemic crisis that includes not only the economic and the energetic, but also the environmental, the entities of the Cuban business system have become aware of the importance of the adoption of urgent solutions that contribute to the preservation of the environment and the very survival of life on the planet. In this context, accounting acquires particular significance, as it constitutes a tool that generates useful information for decision making. The present research, based on the conceptual foundations that express the relationship between accounting and the environment, addresses the analysis of environmental activity in the Cuban rum industry through the case study of the Havana Club International SA-Ronera San José Mixed Company, proposing actions that make possible its registration and control, based on the application of scientific research methods and techniques.